Extreme rainfall frequency analysis based on historical record - Chai, Yijing (Nanyang Technological University, 2023)
This study delves into the complex realm of extreme rainfall events, emphasizing their causes, historical data analysis, and far-reaching impacts, with a specific focus on Singapore and Los Angeles. As global concerns surrounding the effects of global warming on the water cycle intensify, understanding the amplification of extreme rainfall events becomes crucial. The research utilizes a dataset spanning from 1950 to 2022, gathered from ERA5-Land, to analyze and forecast rainfall occurrences across various time intervals, including 10, 50, 100, 1,000, and 10,000 years.